Order and Crash: Multilingual Ecology and Language Planning in Sino-Foreign Cooperative Education Institutions - Wenting Hu (MDPI AG, 2023)
As preconditions and consequences of the globalization of higher education, multilingualism has reconfigured language ecology, language policy and planning, and multilingual management in the contemporary world. However, studies of multilingualism focusing on real-language scenarios in Sino-foreign cooperative education institutions (SCEIs) are rare. This study explores the multilingual ecology, language policy and planning, and language management of three leading SCEIs in China. It also investigates the attitudes of SCEIs' stakeholders toward language use and language policy in multilingual contexts. A case study was conducted by analyzing a significant number of language policy documents, semi-structured interviews with stakeholders, and partial participant observations. The research results reveal the main features of multilingual coexistence and intense competition in the three leading SCEIs by identifying the micro, meso, and macro issues of language management. The effects of language policy and planning mechanisms are also identified in SCEIs of higher education. Potential conflicts in multilingual environments are interpreted from the perspective of global cooperation. Last, recommendations are offered for the advancement of the language evolution of SCEIs in China.